Phytochemical screening and evaluation of antioxidant, total phenolic and flavonoid contents in various weed plants associated with wheat crops - Salim, M.; Saeed, A.; Iqbal, M.; Khan, B. A.; Khan, N.; Rabbani, I.; Alsenani, F.; Rasul, A. (Brazilian journal of biology, 2022)
Abstract This study explores the antioxidant activity, phytochemical screening, total phenolic and flavonoids contents in the extracts of four locally available weeds plants namely Convolvulus arvensis, Chenopodium murale, Avena fatua and Phalaris minor with different solvents. The antioxidant activities of these extracts were determined via various in-vitro methods such as total antioxidant activity (TAA), reducing power (RP), DPPH (2,2-Diphenyl-1-Picrylhydrazyl) free radical scavenging and hydrogen peroxide scavenging assays. Phytochemical screening was performed both qualitatively as well as quantitatively. Total phenolic content (TPC) and total flavonoid content (TFC) were determined through Folin- Ciocalteu reagent and aluminium chloride methods respectively. Methanol-chloroform solvent showed the presence of a high amount of TPC in milligram of gallic acid equivalent per gram of dry weight (mg of GAE/g of DW) in the extracts of all weeds. Their descending sequence was Avena fatua (74.09) ˃ Phalaris minor (65.66) ˃ Chenopodium murale (64.04) ˃ Convolvulus arvensis (61.905), while, chloroform solvent found to be best solvent for the extraction of TFC. Methanol-chloroform solvent was also found to be best solvent for TAA (Total antioxidant activity assay) which showed values in milligram of ascorbic acid equivalent per gram of dry weight (mg of AAE /g of DW), for DPPH scavenging activity, reducing power (antioxidant activity) and hydrogen peroxide scavenging activity. Phytochemical screening indicated the presence of polyphenols, flavonoids, tannins, saponins, alkaloids and glycosides in these weeds. Resumo Este estudo investiga a atividade antioxidante, a triagem fitoquímica, os teores de fenólicos totais e de flavonoides nos extratos de quatro plantas daninhas disponíveis localmente, quais sejam, Convolvulus arvensis, Chenopodium murale, Avena fatua e Phalaris minor com diferentes solventes. As atividades antioxidantes desses extratos foram determinadas por meio de vários métodos in vitro, tais como atividade antioxidante total (TAA), poder redutor (RP), sequestro de radicais livres DPPH (2,2-Difenil-1-Picril-hidrazil) e ensaios de sequestro de peróxido de hidrogênio. A triagem fitoquímica foi realizada tanto qualitativamente quanto quantitativamente. O teor de fenólicos totais (TPC) e o teor de flavonoides totais (TFC) foram determinados pelos métodos do reagente de Folin-Ciocalteu e do cloreto de alumínio, respectivamente. O solvente metanol-clorofórmio mostrou a presença de elevada quantidade de TPC em miligramas de ácido gálico equivalente por grama de peso seco (mg de GAE/g de DW) nos extratos de todas as plantas daninhas. Sua sequência descendente foi Avena fatua (74,09) ˃ Phalaris minor (65,66) ˃ Chenopodium murale (64,04) ˃ Convolvulus arvensis (61,905), enquanto o solvente clorofórmio foi o melhor solvente para a extração de TFC. O solvente metanol-clorofórmio também foi considerado o melhor solvente para AAT (ensaio de atividade antioxidante total), que apresentou valores em miligramas de equivalente de ácido ascórbico por grama de peso seco (mg de AAE/g de DW), para atividade sequestrante de DPPH, RP (atividade antioxidante) e atividade de sequestro de peróxido de hidrogênio. A triagem fitoquímica indicou a presença de polifenóis, flavonoides, taninos, saponinas, alcaloides e glicosídeos nessas plantas daninhas.